Teacher Education For TVET In Europe And Asia: The Comprehensive Requirements - Spöttll, Georg (Journal of Technical Education and Training, 2009)
The training of teachers for vocational education and training (TVET) is a great challenge as numerous countries are not prepared for it. In many countries the opinion still prevails that practical knowledge and skills should be transferred by persons, e.g. skilled workers, with more know-how than the trainees. Therefore it is common practice that Level-3-students in vocational education and training are instructed by Level-4-graduates. Such approaches not only hamper professionalism but are also inefficient. Thus junior teachers are not adequately trained for the required levels. This paper therefore presents an approach for the training of TVET teachers which is based on a professionalized international level and is normally reserved for universities. A professionalized teacher training is based on standards for programmes, contents, and training facilities safeguarding an optimal training of the teaching staff. As teachers are the key persons for meeting the training standards, standards for teacher training must also be discussed. Their quality, their orientation, their design and the consequences for a successful implementation will be discussed. Furthermore it will be shown how standards must be configured in order to be accepted and pursued in a target oriented way by the industry, politics and the target groups themselves. The TT-TVET project will be referred to as well. Within the framework of this project the partners have developed transnational standards which have found utmost acceptance in the partner countries’ own study courses for TVET teachers.